Economic impacts of Brexit to EU27 and UK - Stevović Marko (Industrija, 2018)
Assessment on economic consequences of Brexit to 27 countries members of European Union and to United Kingdom are researched in this paper. The process is current and challenging because some of the negotiating positions are still ongoing. Relevant economic parameters are calculated, analyzed and discussed, as well as spectrum from positive to negative scenarios of United Kingdom withdraw from European Union. Correlation coefficients are calculated and statistical analyses as temporal functions are conducted for gross domestic product of United Kingdom, compared to gross domestic product of European Union with and without United Kingdom. Aspect of trade, import, export, impact on gross domestic product and financial industry are considered with the goal to predict possible economic future for both sides of negotiation.